2021
DOI: 10.3390/mi12121500
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Solution-Processed White Light Emitting Diode Containing a Single Dimeric Copper(I) Emitter Featuring Combined TADF and Phosphorescence

Abstract: Luminescent copper(I) complexes showing thermally activated delayed fluorescence (TADF) have developed to attractive emitter materials for organic light emitting diodes (OLEDs). Here, we study the brightly luminescent dimer Cu2Cl2(P∩N)2 (P∩N = diphenylphosphanyl-6-methyl-pyridine), which shows both TADF and phosphorescence at ambient temperature. A solution-processed OLED with a device structure ITO/PEDOT:PSS/PYD2: Cu2Cl2(P∩N)2/DPEPO (10 nm)/TPBi (40 nm)/LiF (1.2 nm)/Al (100 nm) shows warm white emission with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…A handful of reviews and recent reports that cover the photophysical and photochemical properties of the other types of Cu(I) TADF complexes are available in the literature. 19,22,47,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124] Several examples of [Cu(N^N) 2 ] + and [Cu(N^N)(P^P)] + complexes that exhibit TADF have been reported in the literature. 57,[129][130][131][132][133][134][135][136][137][138][139][140] The photophysical properties of some of these complexes are reported in Table 1.…”
Section: Cu(i) Tadf Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…A handful of reviews and recent reports that cover the photophysical and photochemical properties of the other types of Cu(I) TADF complexes are available in the literature. 19,22,47,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124] Several examples of [Cu(N^N) 2 ] + and [Cu(N^N)(P^P)] + complexes that exhibit TADF have been reported in the literature. 57,[129][130][131][132][133][134][135][136][137][138][139][140] The photophysical properties of some of these complexes are reported in Table 1.…”
Section: Cu(i) Tadf Complexesmentioning
confidence: 99%
“…A handful of reviews and recent reports that cover the photophysical and photochemical properties of the other types of Cu( i ) TADF complexes are available in the literature. 19,22,47,110–124…”
Section: Thermally Activated Delayed Fluorescence (Tadf)mentioning
confidence: 99%
“…The process of EL generation probably proceeds via host‐DSH energy transfer and charge trapping directly on the DSH molecules as is indicated from a comparison of the EL spectra with PL spectra. [ 71,72 ] The latter ones show both PPF and DSH emission. This indicates that radiationless energy transfer is not the dominating process.…”
Section: Electroluminescence Propertiesmentioning
confidence: 99%
“…[5][6][7] Previous reports have indicated that Cu(I)-based complexes with different types of coordinated ligands are able to achieve remarkable luminescence characteristics, including room temperature phosphorescence (RTP) and thermally activated delay fluorescence (TADF). [8][9][10][11][12] Such cuprous complexes show great potential for applications in optoelectronic devices and luminescencebased sensors. [13][14][15][16][17] The d 10 configuration of Cu(I) tends to favor the tetrahedral geometry and extensive studies on Cu(I)-based emitters show that the typical mononuclear four-coordinated Cu(I) complexes generally exhibit inferior luminescence properties.…”
Section: Introductionmentioning
confidence: 99%